Gestos nostálgicos na televisão brasileira: a representação dos programas infantis dos anos 1980 em Samantha! e Verão 90 - Oliveira, Larissa Nascimento Lopes de (2021)
This dissertation proposes to understand how the Brazilian audiovisual products, in their production of meaning, represent children's programs of the 1980s based on the instrumentalization of nostalgias. For this purpose, two contemporary serial fictions that work with nostalgic approaches are listed as a corpus of analysis: the Samantha! (Netflix, 2018-2020) and the soap opera Summer 90 (Rede Globo, 2019). The intention to research these objects is part of a phenomenon, in this case communicational, but also sociological, which has received prominence in the last decade: there is a growing market movement in which companies launch products and services with the appeal of returning to the past (SANTA CRUZ , 2017). In the construction of the theoretical argument, I present a review of studies on nostalgias and its connections with the behavior of contemporary society, addressing questions about modernity, utopias, memory, television and Brazilian identities. After this discussion, the text explores research involving media and nostalgias, discussing nostalgic actions or gestures (NIEMEYER, 2014; LEAL, BORGES and LAGE, 2018; VIEIRA and LOPES, 2020), active nostalgia (FERRAZ, 2017), nostalgia induced by the media (WULF et al., 2018), nostalgic cultural style (GRAINGE, 2000), among other concepts. The objects, their production environments, circuits and reception, are presented together with the description of their plots (FIELD, 2001; NEWMAN, 2006; MCKEE, 2006), and, methodologically, I suggest two categories of analysis: Construction of Protagonists and Scenic Composition. In the first category, from the perspective of Egri (2004) and McKee (2006), I approach the construction of the protagonists and how nostalgies are operationalized through their experiences. In the second, based on the perspectives of Bordwell (2008), Bordwell and Thompson (2013) and Butler (2010), I observe scenarios, costumes, colors, lighting and disposition of characters in children's programs represented in the fictions that they are objects of research. In the end, some nostalgic gestures made by Samantha! and Summer 90 are considered: romantic, satirical, metaimagetic and selfreferential, collective identities and cultural style. When looking at objects and beyond what they exhibit at first glance, it is remarkable to understand that nostalgies are modern phenomenon, ways of nostalgizing through the media are contemporary modern phenomenon. Today we have producers who use nostalgias for too many strands and this phenomenon is positive because it displaces nostalgias for the situation of longing for the past and puts it in front of argumentative positions.